2017
DOI: 10.1111/idj.12284
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in dental out-of-pocket payments among older adult populations: a comparative analysis across selected European countries and the USA

Abstract: Background The current study addresses the extent to which diversity exists in dental out-of-pocket payments across population subgroups within and between the United States and selected European countries. This represents the final paper in a series in which the previous 2 papers addressed diversity in dental coverage and dental utilization, respectively, using similar data and methods. Method We use 2006/2007 HRS and 2004-2006 SHARE data for respondents aged 51 years and older. We estimated the impacts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Additionally, for Slovenia, the likelihood of having the financial burden of dental care was higher for each year spent in paid work. Previous results show that older people with lower educational level and lower income are most likely not to pay any out-of-pocket costs for dental care, and if out-of-pocket payments are made, the amounts are greater for those with higher income and with a higher level of education [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, for Slovenia, the likelihood of having the financial burden of dental care was higher for each year spent in paid work. Previous results show that older people with lower educational level and lower income are most likely not to pay any out-of-pocket costs for dental care, and if out-of-pocket payments are made, the amounts are greater for those with higher income and with a higher level of education [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have confirmed that vulnerable and deprived populations in many countries experience considerable barriers to dental care [12,[14][15][16]. Among those affected, older adults [17,18], individuals with lower income [11,15], and education levels [9,19], those without dental insurance [20,21], and the self-employed [22] are less likely to visit a dentist. Lee et al reported social inequalities in dental care access for periodontal treatments between insured employees and self-employed beneficiaries, with the latter less likely to receive such treatment [23].…”
Section: Introductionmentioning
confidence: 93%
“…France, Switzerland, Denmark, and Sweden, free outpatient care was usually provided only for persons with the lowest-income. 44 A study in 11 European countries (Bulgaria, Estonia, France, Germany, Republic of Ireland, Lithuania, the Netherlands, Poland, Portugal, Slovakia, and Sweden) has reported that emergency dental care, tooth extraction and restorative care for acute pain due to carious lesions were provided in most of these countries. 45 However, root canal treatments, periodontal care and prosthetic restorations either required cost-sharing or were totally out of pocket.…”
Section: Oral Health Provisionmentioning
confidence: 99%
“…There are large disparities among older Europeans about how much they are paying for out‐of‐pocket payments for dental care. In some countries like France, Switzerland, Denmark, and Sweden, free outpatient care was usually provided only for persons with the lowest‐income 44 …”
Section: Introductionmentioning
confidence: 99%